PS-C12-8: BLOOD PRESSURE VARIABILITY IN PREVIOUSLY UNTREATED HYPERTENSIVE PATIENTS RANDOMIZED TO NIFEDIPINE GITS OR RAMIPRIL. REVERENT STUDY. (January 2023) - Bilo, Grzegorz; Kyriakoulis, Konstantinos; Liu, Chang Yuan; Soranna, Davide; Ceravolo, Isabella; Cassago, Silvia; Zhang, Wei; Kollias, Anastasios; Pengo, Martino F; Zambon, Antonella; Wang, Jiguang; Stergiou, George S; et al.
Abstract : Blood pressure (BP) variability (BPV) independently predicts adverse outcomes, making it a potential target for treatment. Preliminary data indicate that dihydropyridine calcium channel blockers (CCB) may reduce BPV more than other antihypertensives. Aim of Reverent: (Reducing blood pressure Variability in Essential hypertension with Ramipril vErsus Nifedipine GITS) Trial was to compare changes in either short-, mid- and long-term BPV in patients treated with a CCB (nifedipine GITS) or an ACE inhibitor (ramipril) in a randomised fashion. Methods: Untreated (treatment-naïve or after treatment washout) patients with mild to moderate essential hypertension and elevated basal BPV, were randomized to open label treatment with nifedipine GITS 30 mg or ramipril 10 mg once daily. BPV after 10 weeks and 12 months of treatment was assessed based on home (primary endpoint; validated AND UA-651BLE monitor), 24-hour ambulatory (A&D TM 2430) and office (AND UA-651BLE) measurements and expressed as standard deviation [SD] of obtained readings. Results: 156 patients were included in the intention-to-treat analysis of the main study (10 weeks, primary analysis) and 138 of the extension study (12 months, exploratory analysis). No significant differences were observed between groups at baseline. Patient characteristics, BP and BPV values after 10 weeks of treatment are reported in the table. No significant differences between groups were observed in home and office BPV at the end of main study, also after adjusting for mean BP reduction. 24-hour weighted SD of systolic BP after 10 weeks of treatment was lower in the nifedipine GITS group (p = 0.032). Exploratory analysis also revealed lower office BPV after 12 months of treatment in nifedipine GITS group (7.15 ± 3.79 vs 9.00 ± 5.28 mmHg, p = 0.026). Conclusions: The study did not identify differences between nifedipine GITS and ramipril in reducing home BPV, while significant differences in favour of nifedipine GITS were observed in 24-hour BPV and in office BPV after 12 months. Clinical impact of these findings remains to be evaluated in outcome studies.